2023
DOI: 10.3389/fneur.2023.1254105
|View full text |Cite
|
Sign up to set email alerts
|

Needs and supporting tools for primary care physicians to improve care of patients with vertigo and dizziness: a national survey

Georgios Mantokoudis,
Andreas Zwergal,
Dierik Heg
et al.

Abstract: BackgroundThe diagnostic workup and treatment decisions for vertigo or dizziness in primary care can be challenging due to the broad range of possible causes and limited time and expertise of physicians. This can lead to delays in treatment and unnecessary tests. We aimed to identify the unmet needs of primary care physicians (PCPs) and strategies to improve care for dizzy patients.Materials and methodsAn online survey was conducted among board-certified PCPs in Switzerland to explore needs in caring for dizzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In this publication, we focused on current limitations, unmet needs, and strategies to overcome difficulties faced by neurologists and ENT physicians involved in the diagnosis and subsequent care of the dizzy patient. We have previously addressed these aspects using a very similar questionnaire from the perspective of primary care physicians (PCPs) ( 9 , 10 ). By identifying these limitations in both primary care physicians and specialists and by proposing tools to improve their interactions, we aim to develop strategies to enhance the care of dizzy patients overall.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this publication, we focused on current limitations, unmet needs, and strategies to overcome difficulties faced by neurologists and ENT physicians involved in the diagnosis and subsequent care of the dizzy patient. We have previously addressed these aspects using a very similar questionnaire from the perspective of primary care physicians (PCPs) ( 9 , 10 ). By identifying these limitations in both primary care physicians and specialists and by proposing tools to improve their interactions, we aim to develop strategies to enhance the care of dizzy patients overall.…”
Section: Discussionmentioning
confidence: 99%
“…While various causes could lead to delayed referral to the specialist (including both patient’s delay and doctor’s delay), reducing the number of patients with no clear diagnosis after the initial assessment of the referring physician will be essential. For PCPs, who provide the initial assessment of the majority of dizzy patients ( 1 ), we have discussed potential strategies to address this limitation in a previous publication ( 9 ). With regards to the continuation of care of the dizzy patient (either by the specialist or the referring physician), approximately half of the specialists indicated that they would like to see the referring physician consistently take back patients for further treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While half of all consultations for dizziness were with primary care physicians (PCPs, 51.9%), significant fractions were seen by specialists such as ear–nose–throat (ENT) physicians (13.3%) and neurologists (9.6%) ( 1 ). Based on a survey performed by primary care physicians in Switzerland, we identified several significant limitations in the care of dizzy patients ( 3 , 4 ). This included infrequent use of state-of-the-art neuro-otological bedside examination techniques, a substantial rate of undiagnosed cases reaching 50% in patients with episodic/chronic dizziness, leading to a high referral rate to specialists both in acutely dizzy patients (30%) and patients with episodic or chronic dizziness (50%), and challenges in the interaction between PCPs and specialists such as long waiting periods ( 4 ).…”
Section: Introductionmentioning
confidence: 99%